Effect of epigallocatechin gallate on the shear bond strength of composite resin to bleached enamel - Zahra Khamverdi; Loghman Rezaei-Soufi; Shahin Kasrei; Abas Moghim Beigi; Shiva Rostami (Isfahan University of Medical Sciences, 2012)
Introduction: There is decreased bond strength of composite resin to bleached enamel. Application of some anti-oxidants reduces the effect of bleaching agents and improves the bond strength of composite resin to enamel. The aim of the present study was to evaluate the effect of epigallocatechin gallat (EGCG) on the shear bond strength of composite resin to bleached enamel. Materials and Methods: Ninety labial surfaces of maxillary incisors were randomly divided into 9 groups after polishing in the present in vitro study as follows: G1: control (no bleaching); G2: bleaching and storage for 24 hours; G3: bleaching and storage for seven days; G4-G6: bleaching and application of 600, 800 and 1000 μmol of EGCG-containing solutions for 10 minutes; G7-G9: bleaching and application of 600, 800 and 1000 μmol of EGCG-containing solutions for 20 minutes. The specimens were bleached with 30% hydrogen peroxide gel for 30 minutes; a composite resin cylinder was bonded on each specimen using a bonding agent. Shear bond strengths of the samples were measured in MPa. Data was analyzed using two-way ANOVA and Mann-Whitney tests (α = 0.05). Results: Maximum (12.98 ± 3.28) and minimum (5.18 ± 1.04) mean shear bond strengths were observed in G1 and G2, respectively. There were no significant effects of time, concentration and their interactions on bond strength (p value > 0.05). Two-by-two comparison of groups did not reveal any significant differences between the groups except for G2 and all the other groups (p value <0.001), G4 and G1 (p value = 0.009), G3 and G4 (p value = 0.015). Conclusion: There is a significant decrease in bond strength of composite to enamel immediately after bleaching. A delay of one week before bonding and use of EGCG might increase bond strength of composite resin to bleached enamel. Key words: Antioxidants, Composite resin, Tea, Tooth bleaching, Bond strength